PENGEMBANGAN DESA WISATA BATIK DI DESA PUNGSARI KABUPATEN SRAGEN JAWA TENGAH - Handayani Dwi Ambarwati; Setiawan Wisnu (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2019)
Abstract: Pungsari Village is a center for batik craftsmen who have long held the title of tourism villages in Sragen Regency. The title of this tourist village is one of the starting points for the growth of the creative economy embryo. These strategies make the environment something important and environmentally sound. In fact, the strategy has been programmed by the Ministry of Village with the theme of Development of Green Tourism Village in 2017. The program scenario has not used a development strategy that slogan